Unraveling The Shields And Swords: The Duel Of Innate And Adaptive Immunity Against Filarial Invaders - Brahmana, Ririn Efranisa Sembiring; Firmansyah, Yohanes (Jurnal Ners, 2024)
The immune system, comprising innate and adaptive components, is crucial for defending the human body against various infectious agents, including filarial parasites. Filariasis, caused by thread-like nematodes, poses a significant health risk in tropical and subtropical regions, affecting over 120 million people worldwide. Understanding the immune response to filarial infection is essential for developing effective treatments and preventive strategies. A comprehensive literature review was conducted, focusing on the human immune response to filarial infections, particularly the roles of the adaptive and innate immune systems. Systematic searches of databases such as PubMed, Scopus, Web of Science, and Google Scholar were carried out, with search terms including "lymphatic filariasis," "immune response to filariasis," and others. The immune response to filarial infection involves complex interactions between the innate and adaptive immune systems. The skin and mucous membranes act as the first line of defense, while specific immune cells and cytokines play crucial roles in the inflammatory response and parasite elimination. The adaptive immune response, particularly the Th2 response, is critical for clearing microfilariae from the bloodstream. However, the immune system's ability to effectively deal with filarial infections varies due to factors such as genetic susceptibilities, infection severity, and environmental exposures.